The Financial Ratios Impact on Earnings Growth of The Consumer Goods Companies Listed on IDX in 2015-2020 - Dyah Nirmala Arum Janie; Rosyati Rosyati (The Accounting Journal of Binaniaga, 2022)
Abstracts. This study examines the effect of financial ratios on the earnings growth of manufacturing companies in the consumer goods industry sector. The analysis was carried out using multiple linear regression using the SPSS 23 program. The company sample data was 102 out of 17 companies in the consumer goods industrial manufacturing sector listed on the Indonesia Stock Exchange (IDX) during the 2015-2020 period. The results of the research that the Current Ratio has a negative and insignificant effect on earnings growth, Net Profit Margin has a positive and significant effect on earnings growth, Total Assets Turnover has a negative and insignificant effect on earnings growth. This study uses earnings growth as the dependent variable, with Current Ratio, Net Profit Margin, Total Assets Turnover as independent variables. It is hoped that future research will test by adding other variables that affect earnings growth.Keywords: Earnings Growth, Current Ratio, Net Profit Margin, Total Assets Turnover.